Devolution and Regional Development in the United Kingdom - MacKinnon, Danny (Redes, 2009)
Since the 1970s, many different governments around the world have sought to transfer power to sub-state governments, meaning that devolution has become a key ‘global trend’ of recent decades (Rodriguez-Pose and Gill, 2003). The term devolution can be defined as a form of political decentralisation, involving a “transfer of power downwards to political authorities at immediate or local levels” (Agranoff, 2004, p.26). Devolution has introduced in response to pressures exerted on established states from both ‘below’ and ‘above’, referring to demands from regions within the state for more say over their own affairs and the effects of processes of globalisation and supra-national integration respectively (Keating, 1997; Tomaney, 2000). Arguments for devolution have variously stressed questions of identity in relation to the recognition of minority groups, governance in terms of creating more effective political institutions, and the economy by allowing regions to adapt to changes in the economic environment and to fulfil their economic potential (Rodriguez-Pose and Sandall, 2008).